FRI0180 Paraneoplasic antiphospholipid syndrome- a possible main cause of thrombosis in cancer patients. (1st June 2001) - Tanaseanu, C; Tanaseanu, S; Urban, A; Popescu, M; Hanganu, D; Cojan, A
Abstract : Background: The antiphospholipid (APS) is a hypercoagulable state marked by the antibodies that recognise anionic phospholipid-protein cofactor complexes. Objectives: This study was undertaken to investigate a possible association of antiphospholipid antibodies (APLA) in cancer patients with thromboembolic events. Methods: The study group included 46 patients with different malignancies and associated thromboses. Tests were performed for detecting APLA: anticardiolipin enzyme ?linked immunoassay (ELISA) for both IgG and IgM isotypes, antiâ2-GPI IgG antibody ELISA, and coagulation test for lupus anticoagulant (LAC). We used ACL method with IL Test LAC Screen and IL Test LAC Confirm. All patients underwent complete clinical and radiological examination, routine laboratory tests were done. Results: 18 patients had APS associated with evolutive cancers. LAC was present in 14 patients (B-cell lymphoma (2 cases), ovarian-(3), breast-(3), lung-(4), pancreatic-(1), bladder (1) cancer, and was related mainly with deep vein thromboses of the legs, pulmonary embolism and catastrophic antiphospholipid syndrome. Anticardiolipin antibodies (ACLA) were detected in 3 patients with bladder -, pancreatic – and breast cancer, and were associated with aortic nonocclusive thrombosis, stroke, myocardial infarction and multiinfarct dementia. In one patient (prostatic cancer) were present both ACLA and LAC, associated with stroke, myocardial infarction, multiinfarct dementia. The presence of LAC seems to be related more to venous thromboses and metastatic disease, while ACLA seems to be related to arterial thromboses. Conclusion: The presence of APS in cancer patients is associated with vascular thromboses, leading to a poor quality of life or to fatal events (including metastatic spread). The presence of APLA in cancer patients may be a warning sign of a thrombotic event and might lead to a better selection of patients for prophylactic anticoagulant therapy.